The reception of the Categories of Aristotle, c. 80 BC to AD 220 - Griffin, M; Michael Griffin (2009)
This thesis focuses on the ancient reception of the Categories of Aristotle, a work which served continuously, from late antiquity into the early modern period (Frede 1987), as the student’s introduction to philosophy.  There had previously been no comprehensive study of the reception of the Categories during the age of the first philosophical commentaries (c. 80 BC to AD 220). In this study, I have collected, assigned, and analyzed the relevant fragments of commentary belonging to this period, including some that were previously undocumented or inexplicit in the source texts, and sought to establish and characterize the influence of the early commentators’ activity on the subsequent Peripatetic tradition. In particular, I trace the early evolution of criticism and defense of the text through competing accounts of its aim (skopos), which would ultimately lead Stoic and Platonic philosophers to a partial acceptance of the Categories and frame its role in the later Neo-Platonic curriculum.